Using rival effects to identify synergies and improve merger typologies - Joseph A. Clougherty; Tomaso Duso (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2011)
The strategy literature has found it difficult to differentiate between collusive and efficiencybased synergies in horizontal merger activity. We propose a theoretically-backed methodological approach to classify mergers that yields more information on merger types and merger effects, and that can, moreover, distinguish between mergers characterized largely by collusion-based synergies and mergers characterized largely by efficiency-based synergies. Crucial to the proposed measurement approach is that it encompasses the impact of merger events not only on merging firms (custom in the literature), but also on non-merging rival firms (novel in the literature). Employing the event-study procedure with stock-market data on samples of large horizontal mergers drawn from the US and UK (an Anglo-American sub-sample) and from the European continent, we demonstrate how the proposed schematic can better clarify the nature of merger activity.
Keywords: 330; acquisitions; event-study; mergers; research methods; rivals; synergy; Fusion; Horizontale Konzentration; Synergie; Wettbewerb; Schätzung; EU-Staaten; Großbritannien; USA